1994
DOI: 10.1073/pnas.91.18.8472
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between docetaxel (Taxotere) and Plasmodium falciparum-infected erythrocytes.

Abstract: Taxotere (docetaxel) inhibits Plasmodiumfalciparum erythrocytic development in vitro at nanomolar concentrations, both In chloroqulne-sensitive (F32/Tanzania) and chloroquine-resistant (FcBl/Colombia, FcR3/Gambia) strains. The dose-response assays performed on asynchronous cultures during 42 hr showed clear biphasic curves with a plateau from 50 pM to 10 nM and a single sigmoid curve with a concentration inhibiting 50% of growth (IC50) 8472The publication costs of this article were defrayed in part by page ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 25 publications
1
26
0
Order By: Relevance
“…Nevertheless diffused micro-punctate structures observed in curcumin treated fixed parasites (Figure 6 B, C) might represent accumulated unpolymerized tubulin. This would be similar to observations with other microtubule disrupting drugs tested in P. falciparum [27], [35], [58] illustrated in Figure 7A, and different from the thick rods of microtubules observed after paclitaxel treatment, a tubulin stabilizing agent [22], [23], [59], [60] and Figure 7B. Interestingly, the figures are suggestive of the fact that although spindle structures are affected, there seems to be no difference in the outcome as far as the division of the nucleus is concerned.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Nevertheless diffused micro-punctate structures observed in curcumin treated fixed parasites (Figure 6 B, C) might represent accumulated unpolymerized tubulin. This would be similar to observations with other microtubule disrupting drugs tested in P. falciparum [27], [35], [58] illustrated in Figure 7A, and different from the thick rods of microtubules observed after paclitaxel treatment, a tubulin stabilizing agent [22], [23], [59], [60] and Figure 7B. Interestingly, the figures are suggestive of the fact that although spindle structures are affected, there seems to be no difference in the outcome as far as the division of the nucleus is concerned.…”
Section: Discussionsupporting
confidence: 88%
“…Previously, treatment with microtubule inhibitors has been shown to lead to abnormal morphology of the parasites in vitro [22], [23]. To analyze the gross effects of curcumin on parasite morphology, 5 µM curcumin treated cultures were compared with untreated cultures.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gligorov and Lotz [20] reported that taxane at high concentrations, especially paclitaxel and docetaxel, interferes with cell development by inhibiting nuclear and cytoplasmic maturation, thus reducing the cell development rate [39,45]. Moreover, Schrével et al [37] reported that docetaxel at concentrations P0.5 lM inhibited cell development due to binding between docetaxel and tubulin of microtubules, which leads to the stabilization of the polymerization process. This results in the loss of balance between microtubules and tubulin, thus causing interference with the function of key enzymes such as cyclin, which is responsible for stimulating cyclin-dependent kinases (CDKs) and maturation-promoting factor (MPF).…”
Section: Discussionmentioning
confidence: 95%
“…Briefly, at 2 h after warming, oocytes freed from cumulus cells were fixed in 3% paraformaldehyde supplemented with 0.6% Triton X-100 in mDPBS with 0.1% polyvinyl alcohol (PP) [37] for 30 min. Subsequently, they were washed three times in PP and blocked in 3% goat serum in PP for 45 min.…”
Section: Microtubule (Mt) and Chromosome (Cm) Stainingmentioning
confidence: 99%